# Table of Integrals

Basic Forms

x
n
dx =
1
n + 1
x
n+1
+ c (1)

1
x
dx = ln x + c (2)

udv = uv −

vdu (3)

1
ax + b
dx =
1
a
ln |ax + b| + c (4)
Integrals of Rational Functions

1
(x + a)
2
dx = −
1
x + a
+ c (5)

(x + a)
n
dx =
(x + a)
n+1
n + 1
+ c, n = −1 (6)

x(x + a)
n
dx =
(x + a)
n+1
((n + 1)x −a)
(n + 1)(n + 2)
+ c (7)

1
1 + x
2
dx = tan
−1
x + c (8)

1
a
2
+ x
2
dx =
1
a
tan
−1
x
a
+ c (9)

x
a
2
+ x
2
dx =
1
2
ln |a
2
+ x
2
| + c (10)

x
2
a
2
+ x
2
dx = x −a tan
−1
x
a
+ c (11)

x
3
a
2
+ x
2
dx =
1
2
x
2

1
2
a
2
ln |a
2
+ x
2
| + c (12)

1
ax
2
+ bx + c
dx =
2

4ac −b
2
tan
−1
2ax + b

4ac −b
2
+ C (13)

1
(x + a)(x + b)
dx =
1
b −a
ln
a + x
b + x
, a = b (14)

x
(x + a)
2
dx =
a
a + x
+ ln |a + x| + C (15)

x
ax
2
+ bx + c
dx =
1
2a
ln |ax
2
+ bx + c|

b
a

4ac −b
2
tan
−1
2ax + b

4ac −b
2
+ C (16)
Integrals with Roots

2
3
(x −a)
3/2
+ C (17)

1

x ±a
dx = 2

x ±a + C (18)

1

a −x
dx = −2

a −x + C (19)

x

2
3
a(x −a)
3/2
+
2
5
(x −a)
5/2
+ C (20)

ax + bdx =

2b
3a
+
2x
3

ax + b + C (21)

(ax + b)
3/2
dx =
2
5a
(ax + b)
5/2
+ C (22)

x

x ±a
dx =
2
3
(x ±2a)

x ±a + C (23)

x
a −x
dx = −

x(a −x)
−a tan
−1

x(a −x)
x −a
+ C (24)

x
a + x
dx =

x(a + x)
−a ln

x +

x + a

+ C (25)

x

ax + bdx =
2
15a
2
(−2b
2
+ abx + 3a
2
x
2
)

ax + b + C (26)

x(ax + b)dx =
1
4a
3/2

(2ax + b)

ax(ax + b)
−b
2
ln

a

x +

a(ax + b)

+ C (27)

x
3
(ax + b)dx =
¸
b
12a

b
2
8a
2
x
+
x
3

x
3
(ax + b)
+
b
3
8a
5/2
ln

a

x +

a(ax + b)

+ C (28)

c 2007. From http://integral-table.com, last revised February 16, 2009. This material is provided as is without warranty or representation
about the accuracy, correctness or suitability of this material for any purpose. Some restrictions on use and distribution may apply, including the
terms of the Creative Commons Attribution-Noncommercial-Share Alike 3.0 Unported License. See the web site for details. The formula numbers
on this document may be diﬀerent from the formula numbers on the web page.
1

x
2
±a
2
dx =
1
2
x

x
2
±a
2
±
1
2
a
2
ln

x +

x
2
±a
2

+ C (29)

a
2
−x
2
dx =
1
2
x

a
2
−x
2
+
1
2
a
2
tan
−1
x

a
2
−x
2
+ C (30)

x

x
2
±a
2
dx =
1
3

x
2
±a
2

3/2
+ C (31)

1

x
2
±a
2
dx = ln

x +

x
2
±a
2

+ C (32)

1

a
2
−x
2
dx = sin
−1
x
a
+ C (33)

x

x
2
±a
2
dx =

x
2
±a
2
+ C (34)

x

a
2
−x
2
dx = −

a
2
−x
2
+ C (35)

x
2

x
2
±a
2
dx =
1
2
x

x
2
±a
2

1
2
a
2
ln

x +

x
2
±a
2

+ C (36)

ax
2
+ bx + cdx =
b + 2ax
4a

ax
2
+ bx + c
+
4ac −b
2
8a
3/2
ln

2ax + b + 2

a(ax
2
+ bx
+
c)

+ C (37)

x

ax
2
+ bx + c =
1
48a
5/2

2

a

ax
2
+ bx + c

3b
2
+ 2abx + 8a(c + ax
2
)

+3(b
3
−4abc) ln

b + 2ax + 2

a

ax
2
+ bx + x

(38)

1

ax
2
+ bx + c
dx =
1

a
ln

2ax + b + 2

a(ax
2
+ bx + c)

+ C (39)

x

ax
2
+ bx + c
dx =
1
a

ax
2
+ bx + c
+
b
2a
3/2
ln

2ax + b + 2

a(ax
2
+ bx + c)

+ C (40)
Integrals with Logarithms

ln axdx = xln ax −x + C (41)

ln ax
x
dx =
1
2
(ln ax)
2
+ C (42)

ln(ax + b)dx =

x +
b
a

ln(ax + b) −x + C, a = 0 (43)

ln

a
2
x
2
±b
2

dx = xln

a
2
x
2
±b
2

+
2b
a
tan
−1
ax
b
−2x + C (44)

ln

a
2
−b
2
x
2

dx = xln

ar −b
2
x
2

+
2a
b
tan
−1
bx
a
−2x + C (45)

ln

ax
2
+ bx + c

dx =
1
a

4ac −b
2
tan
−1
2ax + b

4ac −b
2
−2x +

b
2a
+ x

ln

ax
2
+ bx + c

+ C (46)

xln(ax + b)dx =
bx
2a

1
4
x
2
+
1
2

x
2

b
2
a
2

ln(ax + b) + C (47)

xln

a
2
−b
2
x
2

dx = −
1
2
x
2
+
1
2

x
2

a
2
b
2

ln

a
2
−b
2
x
2

+ C (48)
Integrals with Exponentials

e
ax
dx =
1
a
e
ax
+ C (49)

xe
ax
dx =
1
a

xe
ax
+
i

π
2a
3/2
erf

i

ax

+ C,
where erf(x) =
2

π

x
0
e
−t
2
dtet (50)

xe
x
dx = (x −1)e
x
+ C (51)

xe
ax
dx =

x
a

1
a
2

e
ax
+ C (52)

x
2
e
x
dx =

x
2
−2x + 2

e
x
+ C (53)
2

x
2
e
ax
dx =

x
2
a

2x
a
2
+
2
a
3

e
ax
+ C (54)

x
3
e
x
dx =

x
3
−3x
2
+ 6x −6

e
x
+ C (55)

x
n
e
ax
dx =
(−1)
n
a
n+1
Γ[1 + n, −ax],
where Γ(a, x) =

x
t
a−1
e
−t
dt (56)

e
ax
2
dx = −
i

π
2

a
erf

ix

a

(57)
Integrals with Trigonometric Functions

sin axdx = −
1
a
cos ax + C (58)

sin
2
axdx =
x
2

sin 2ax
4a
+ C (59)

sin
n
axdx =

1
a
cos ax
2
F
1
¸
1
2
,
1 −n
2
,
3
2
, cos
2
ax

+ C (60)

sin
3
axdx = −
3 cos ax
4a
+
cos 3ax
12a
+ C (61)

cos axdx =
1
a
sin ax + C (62)

cos
2
axdx =
x
2
+
sin 2ax
4a
+ C (63)

cos
p
axdx = −
1
a(1 + p)
cos
1+p
ax×
2
F
1
¸
1 + p
2
,
1
2
,
3 + p
2
, cos
2
ax

+ C (64)

cos
3
axdx =
3 sin ax
4a
+
sin 3ax
12a
+ C (65)

cos axsin bxdx =
cos[(a −b)x]
2(a −b)

cos[(a + b)x]
2(a + b)
+ C, a = b (66)

sin
2
axcos bxdx = −
sin[(2a −b)x]
4(2a −b)
+
sin bx
2b

sin[(2a + b)x]
4(2a + b)
+ C (67)

sin
2
xcos xdx =
1
3
sin
3
x + C (68)

cos
2
axsin bxdx =
cos[(2a −b)x]
4(2a −b)

cos bx
2b

cos[(2a + b)x]
4(2a + b)
+ C (69)

cos
2
axsin axdx = −
1
3a
cos
3
ax + C (70)

sin
2
axcos
2
bxdx =
x
4

sin 2ax
8a

sin[2(a −b)x]
16(a −b)
+
sin 2bx
8b

sin[2(a + b)x]
16(a + b)
+ C (71)

sin
2
axcos
2
axdx =
x
8

sin 4ax
32a
+ C (72)

tan axdx = −
1
a
ln cos ax + C (73)

tan
2
axdx = −x +
1
a
tan ax + C (74)

tan
n
axdx =
tan
n+1
ax
a(1 + n)
×
2
F
1

n + 1
2
, 1,
n + 3
2
, −tan
2
ax

+ C (75)

tan
3
axdx =
1
a
ln cos ax +
1
2a
sec
2
ax + C (76)

sec xdx = ln | sec x + tan x| + C
= 2 tanh
−1

tan
x
2

+ C (77)

sec
2
axdx =
1
a
tan ax + C (78)

sec
3
xdx =
1
2
sec xtan x +
1
2
ln | sec xtan x| + C (79)

sec xtan xdx = sec x + C (80)

sec
2
xtan xdx =
1
2
sec
2
x + C (81)

sec
n
xtan xdx =
1
n
sec
n
x + C, n = 0 (82)

csc xdx = ln

tan
x
2

+ C = ln | csc x −cot x| + C (83)
3

csc
2
axdx = −
1
a
cot ax + C (84)

csc
3
xdx = −
1
2
cot xcsc x +
1
2
ln | csc x −cot x| + C (85)

csc
n
xcot xdx = −
1
n
csc
n
x + C, n = 0 (86)

sec xcsc xdx = ln | tan x| + C (87)
Products of Trigonometric Functions and Monomials

xcos xdx = cos x + xsin x + C (88)

xcos axdx =
1
a
2
cos ax +
x
a
sin ax + C (89)

x
2
cos xdx = 2xcos x +

x
2
−2

sin x + C (90)

x
2
cos axdx =
2xcos ax
a
2
+
a
2
x
2
−2
a
3
sin ax + C (91)

x
n
cosxdx = −
1
2
(i)
n+1
[Γ(n + 1, −ix)
+(−1)
n
Γ(n + 1, ix)] + C (92)

x
n
cosaxdx =
1
2
(ia)
1−n
[(−1)
n
Γ(n + 1, −iax)
−Γ(n + 1, ixa)] + C (93)

xsin xdx = −xcos x + sin x + C (94)

xsin axdx = −
xcos ax
a
+
sin ax
a
2
+ C (95)

x
2
sin xdx =

2 −x
2

cos x + 2xsin x + C (96)

x
2
sin axdx =
2 −a
2
x
2
a
3
cos ax +
2xsin ax
a
2
+ C (97)

x
n
sin xdx = −
1
2
(i)
n
[Γ(n + 1, −ix)
−(−1)
n
Γ(n + 1, −ix)] + C (98)
Products of Trigonometric Functions and
Exponentials

e
x
sin xdx =
1
2
e
x
(sin x −cos x) + C (99)

e
bx
sin axdx =
1
a
2
+ b
2
e
bx
(b sin ax −a cos ax) + C (100)

e
x
cos xdx =
1
2
e
x
(sin x + cos x) + C (101)

e
bx
cos axdx =
1
a
2
+ b
2
e
bx
(a sin ax + b cos ax) + C (102)

xe
x
sin xdx =
1
2
e
x
(cos x −xcos x + xsin x) + C (103)

xe
x
cos xdx =
1
2
e
x
(xcos x −sin x + xsin x) + C (104)
Integrals of Hyperbolic Functions

cosh axdx =
1
a
sinh ax + C (105)

e
ax
cosh bxdx =

e
ax
a
2
−b
2
[a cosh bx −b sinh bx] + C a = b
e
2ax
4a
+
x
2
+ C a = b
(106)

sinh axdx =
1
a
cosh ax + C (107)

e
ax
sinh bxdx =

e
ax
a
2
−b
2
[−b cosh bx + a sinh bx] + C a = b
e
2ax
4a

x
2
+ C a = b
(108)

e
ax
tanh bxdx =

e
(a+2b)x
(a + 2b)
2
F
1

1 +
a
2b
, 1, 2 +
a
2b
, −e
2bx

1
a
e
ax
2
F
1

a
2b
, 1, 1E, −e
2bx

+ C a = b
e
ax
−2 tan
−1
[e
ax
]
a
+ C a = b
(109)

tanh bxdx =
1
a
ln cosh ax + C (110)

cos axcosh bxdx =
1
a
2
+ b
2
[a sin axcosh bx
+b cos axsinh bx] + C (111)
4

cos axsinh bxdx =
1
a
2
+ b
2
[b cos axcosh bx+
a sin axsinh bx] + C (112)

sin axcosh bxdx =
1
a
2
+ b
2
[−a cos axcosh bx+
b sin axsinh bx] + C (113)

sin axsinh bxdx =
1
a
2
+ b
2
[b cosh bxsin ax−
a cos axsinh bx] + C (114)

sinh axcosh axdx =
1
4a
[−2ax + sinh 2ax] + C (115)

sinh axcosh bxdx =
1
b
2
−a
2
[b cosh bxsinh ax
−a cosh axsinh bx] + C (116)
5